2018
DOI: 10.1186/s12913-018-3223-6
|View full text |Cite
|
Sign up to set email alerts
|

‘MATRI-SUMAN’ a capacity building and text messaging intervention to enhance maternal and child health service utilization among pregnant women from rural Nepal: study protocol for a cluster randomised controlled trial

Abstract: BackgroundCapacity development of health volunteers and text messaging to pregnant women through mobile phones have shown improved maternal and child health (MCH) outcomes and is associated with increased utilisation of MCH services. However, such interventions are uncommon in Nepal. We aim to carry out an intervention with the hypothesis that capacity building and text messaging intervention will increase the MCH service utilisation.Method/designMATRI-SUMAN is a 12-month cluster randomized controlled trial (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Interestingly, having access to a kitchen garden at home provides opportunities to increase dietary diversity and consume green leafy vegetables during pregnancy [ 52 ]. This study also revealed that mothers in the intervention area were found to be at a lower risk of having an LBW baby, indicating the beneficial effects of MATRI-SUMAN intervention [ 23 ] in lowering LBW cases.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, having access to a kitchen garden at home provides opportunities to increase dietary diversity and consume green leafy vegetables during pregnancy [ 52 ]. This study also revealed that mothers in the intervention area were found to be at a lower risk of having an LBW baby, indicating the beneficial effects of MATRI-SUMAN intervention [ 23 ] in lowering LBW cases.…”
Section: Discussionmentioning
confidence: 74%
“…Pregnant women received periodic health promotion texts about maternal and child health (MCH) components, via a mobile messaging service, while participants in the control group received the usual care. Details of the study design have been reported in a previously published paper [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of mobile phone and wireless technology has a huge potential to improve the health and wellbeing of the resource constraint communities through communication and exchange of skills among health workers and with communities [30,31]. The use of the mobile application to improve maternal and neonatal health outcomes has been studied among FCHVs in Baglung and Dhanusha districts of Nepal which also has shown promising results [32][33][34]. This might be because FCHVs are likely to be contacted through mobile phone in case of emergency or other health needs by the communities leading to increased service utilization of child health services [33].…”
Section: Discussionmentioning
confidence: 99%
“…We employed community-based cross-sectional study design. We used baseline data obtained from the ‘MATRI-SUMAN’, a randomized controlled trial of a capacity building and text messaging intervention designed to enhance maternal and child health service utilization among pregnant women residing in rural Nepal [ 19 ]. The baseline data included socio-demographic information and CVD risk factors - tobacco use, alcohol consumption, fruits and vegetables intake and physical activities.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 453 eligible pregnant women, 426 gave consent to participate in the study. The details of study design can be found elsewhere [ 19 ].…”
Section: Methodsmentioning
confidence: 99%